Biotechnology and Conservation of Cultural Heritage - Palla, Franco; Barresi, Giovanna (Cham : Springer International Publishing : Imprint: Springer, 2022)
This second fully updated and extended edition of Biotechnology and Conservation of Cultural Heritage provides in-depth insights into the role of different microorganisms and microbial compounds in biodeterioration, conservation and restoration of artworks and artifacts. Latest methods to detect, remove and prevent microbial colonization on artwork surfaces and in air environments of libraries and museums are discussed and illustrated by engaging case studies. Furthermore, this edition covers new case studies on Archaeobiology, exploring ways to perform the molecular biology characterization, restoring and protecting museum taxidermal specimens, preserving and guaranteeing the future integrity. Finally, the use of halloysite-nanotubes is investigated to set up innovative protocols in consolidation and long-term protection of waterlogged and archaeological wood. This book addresses to Biologists, Microbiologists, Conservation Scientists and Conservators who are interested in understanding the role of microorganisms and bioactive molecules in conservation projects. .
Chapter 1: Biodeterioration -- Chapter 2: Bioaerosol -- Chapter 3: Biocide -- Chapter 4: Biocleaning -- Chapter 5: Innovative and integrate strategies. Case studies -- Chapter 6: Taxidermal preparations of an extinct Sicilian wolf population (Canis lupus Linnaeus, 1758): Biological studies and Restoration.
Keywords: Industrial microbiology; Cultural property-Protection.; Historic preservation; Biofilms; Microbial ecology; Industrial Microbiology; Conservation and Preservation; Biofilms; Environmental Microbiology